Climate change and water supply: governance and adaptation planning in Florida - Robert G. Maliva (IWA Publishing, 2021)
Florida has been described as ‘ground zero’ for climate change in the United States with coastal communities vulnerable to sea-level rise and water supplies under threat from saline-water intrusion, changes in precipitation amounts and patterns, and temperature-driven increases in demands. Water utilities and regional suppliers are responsible for their own water supply plans and adaptation strategies, which are developed largely by a relatively small group of technical specialists (internal and contracted). Water supply planning is prescribed by the state water governance system and local community planning processes. The degree of engagement of large coastal communities and water utilities and regional water suppliers in Florida with climate change research is generally high. Climate change-induced impacts to water supplies and demands over the common 20-year planning horizon are likely to be small relative to increases in demand caused by projected on-going population growth and normal climatic variation. Water utilities in Florida have been incidentally moving toward more climate-resilient supplies (e.g., brackish groundwater desalination) due to the unavailability of additional permittable, inexpensive fresh groundwater rather than climate change concerns. Climate change will narrow the alternatives for future water-supply development. Highlights Addresses adaptation of water supply to climate change in Florida, a state with a high vulnerability to climate change.; Addresses how regulatory frameworks impact the adaptation process.; Discusses how adaptation of water supplies to increased demands from population growth results in increased resilience to climate change.;